Developing professional identity through group experiential learning: A Group-Analytic experiential training approach for use with postgraduate clinical psychology students. Issue 2 (3rd April 2019) - Di Stefano, Giovanni; Ruvolo, Giuseppe; Lo Mauro, Valentina
Abstract : This article describes a Group-Analytic, experiential and non-directive training approach taken with postgraduate clinical psychology students in training. Based on median/large group settings, it is aimed at promoting the development of psychology students' professional identities. It uses a particular form of experiential learning beyond the rational and cognitive aspects of traditional didactic teaching in order to stimulate students' own involvement in the integration of their thoughts, feelings and attitudes. From a Group-Analytic perspective, the group is conceived of as an organic entity. The convenor takes up a less intrusive and non-directive role in comparison to a traditional seminar leader. The learning outcomes that may be obtained with this group model are outlined in a description of group process below, and through the content analysis of verbalizations of students who participated in the twelve-session experiential group. The results confirm the usefulness of the Group-Analytic experiential training approach, highlighting the construction of professional self-awareness, achieved through students exploring their own relationship modalities in an intersubjective learning space.